ANALISIS KOMPARATIF RISIKO PRODUKTIVITAS, DAN EFISIENSI PRODUKSI KELAPA SAWIT PTPN III DAN PTPN XIV (PERSERO) - , Ir. Lili Dahliani, MM., Msi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of the research is to analyse the risk, productivity, and production eficiency Palm Oil in PTPN III and PTPN XIV (Corp.) is to compare and to analize the risks and affecting factors, effect of the risk to the productivity, productivity and its affecting factors, production efficiency and CPO rendemen of both PTPN III and PTPN XIV with different performance. The analysis data was conducted by differentiation test (T-Test) of the medium index (t-test), factor analysis that affect production risk using Just and Pope model, panel data analysis on risk influence to productivity and factors that affect Fresh Palm Oil (FPO) productivity, also eficiency analysis using production Frontier Statistic Stokastik function approach. The result of the study showed that FPO productivity risk level in PTPN III is contradictorily different and lower (0.033078) than the FPO productivity risk level in PTPN XIV (0.314942)